Pengaruh Inflasi dan Kinerja Keuangan Perusahaan terhadap Pembiayaan pada Bank Umum Syariah (Tahun 2015-2018) - Trisnia Widuri; Nuraidya Fajariah (Universitas Islam Kadiri, 2019)
This study aims to determine the effect of several variables both monetary and performance variables on sharia financing in Islamic Commercial Banks in Indonesia. The data used is the Time Series data from January 2015 to July 2018, sourced from the Islamic Banking Statistics data. To analyze the effect of independent variables on the dependent variable, the author uses the Multiple Linear Regression method. The results showed that the inflation variable as a monetary variable had a significant negative effect on Islamic finance by Islamic Commercial Banks, the company performance variable, FDR and NPL had a significant negative effect on Islamic finance while ROA and CAR had a non-significant effect on Islamic finance.